Supercritical carbon dioxide: a solvent like no other - Peach, Jocelyn; Eastoe, Julian (Beilstein Journal of Organic Chemistry, 2014)
Supercritical carbon dioxide (scCO2) could be one aspect of a significant and necessary movement towards green chemistry, being a potential replacement for volatile organic compounds (VOCs). Unfortunately, carbon dioxide has a notoriously poor solubilising power and is famously difficult to handle. This review examines attempts and breakthroughs in enhancing the physicochemical properties of carbon dioxide, focusing primarily on factors that impact solubility of polar and ionic species and attempts to enhance scCO2 viscosity.
Keywords: CO2 chemistry; microemulsion; self-assembly; supercritical CO2; surfactant; viscosity